2000
DOI: 10.1007/bf03018851
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of carboxyhe-moglobin dilution method for the measurement of circulating blood volume

Abstract: The CO method can measure BVc with a similar degree of accuracy as the 51Cr method. It is simple, repeatable and safe without the risk of exposure to radioactivity in the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Commonly used techniques for determination of blood volume are radioactive indicators, dye-dilution methods or carbon monoxide labelling of haemoglobin (Hb) following carbon monoxide rebreathing (Ertl et al 2007). Carbon monoxide rebreathing has been shown to have similar accuracy, sensitivity and variability as the gold standard radioactive methods (Burge and Skinner 1995; Ohki et al 2000). The accuracy of the carbon monoxide rebreathing method stands on the reliability and precision in measuring changes in carboxyhaemoglobin (COHb) saturation (Gore et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used techniques for determination of blood volume are radioactive indicators, dye-dilution methods or carbon monoxide labelling of haemoglobin (Hb) following carbon monoxide rebreathing (Ertl et al 2007). Carbon monoxide rebreathing has been shown to have similar accuracy, sensitivity and variability as the gold standard radioactive methods (Burge and Skinner 1995; Ohki et al 2000). The accuracy of the carbon monoxide rebreathing method stands on the reliability and precision in measuring changes in carboxyhaemoglobin (COHb) saturation (Gore et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the carbon monoxide (CO) rebreathing method has been improved several times (Thomsen et al 1991;Burge and Skinner 1995;H€ utler et al 2000;Schmidt and Prommer 2005;Gore et al 2006;Siebenmann et al 2017), and the application of this method has been reported in many studies. The accuracy of the CO dilution method has been shown to be similar to that of the 51 CR method (Fukui and Shigemi 1989;Ohki et al 2000). CO binds almost completely to hemoglobin.…”
Section: Introductionmentioning
confidence: 72%
“…The accuracy of the CO dilution method has been shown to be similar to that of the 51 CR method (Fukui and Shigemi ; Ohki et al. ). CO binds almost completely to hemoglobin.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…17 In that paper, we simultaneously measured BVc using the 51 Cr method as well as the CO method and verified the accuracy and precision of the CO method by comparing the values obtained from the CO method with those from the 5 1 Cr method which is widely accepted as a standard method for BVc measurement. Small mean differences and standard deviations between the CO method and the 5 1 Cr method (-70.2 ± 184.8 ml) and small percentage errors (-0.49 ± 1.29%) indicated the accuracy and precision of the CO method, and a close correlation was observed (r=0.97).…”
Section: Measurement Of Bvc the Co Methodsmentioning
confidence: 84%